2006
DOI: 10.1592/phco.26.4.493
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Previous Antiplatelet Drug Use in Patients with New or Recurrent Ischemic Stroke: Buffalo Metropolitan Area and Erie County Stroke Study

Abstract: The relatively high proportion of patients who developed ischemic stroke despite taking antiplatelet drugs observed in this regional hospital-based study mandates clinical trials specifically addressing therapeutic intervention for this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
(18 reference statements)
1
10
0
Order By: Relevance
“…Also, such patients are known to have more cerebrovascular risk factors. 29 Similarly to previous studies, we observed an independent association between stroke mechanism and recurrence risk. 9,30 Most closely related to recurrence was the category of other determined cause (mostly rare causes), indicating that underlying systemic disease such as cancer, endocarditis or vasculitis may lead to an inherently high recurrence rate or are non-responsive to current treatment strategies.…”
Section: Discussionsupporting
confidence: 90%
“…Also, such patients are known to have more cerebrovascular risk factors. 29 Similarly to previous studies, we observed an independent association between stroke mechanism and recurrence risk. 9,30 Most closely related to recurrence was the category of other determined cause (mostly rare causes), indicating that underlying systemic disease such as cancer, endocarditis or vasculitis may lead to an inherently high recurrence rate or are non-responsive to current treatment strategies.…”
Section: Discussionsupporting
confidence: 90%
“…20 Qureshi et al reported a high proportion of patients who developed ischemic stroke despite receiving antiplatelet drugs, in their regional hospital-based study. 21 CAST and the similarly large International Stroke Trial (IST) showed reliably that aspirin started early in hospital produces a small but definite net benefit, with approximately 9±3 fewer deaths or non-total strokes per 1,000 in the first few weeks and with 13±5 fewer dead or dependent per 1,000 after some weeks or months of followup. 7 As an observational perspective study, the current largest stroke registry program in China revealed the benefit of long-term antiplatelet therapy after ischemic stroke, which is consistent with that demonstrated in other populations.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses of randomized clinical trials indicate that the combination of aspirin plus dipyridamole is the preferred antiplatelet regimen, reducing the risk of recurrent vascular events to 34% among patients with TIA and ischemic stroke of arterial origin [24] . However, in a regional hospital-based study, Qureshi et al [25] reported a higher proportion of patients who developed ischemic stroke despite taking antiplatelet drugs. Observational prospective studies in China, the current study, and the Nanjing Stroke Registry Program came to the conclusion that antiplatelet therapy was associated with decreased risk of the occurrence of a further vascular event after acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 98%